2007
DOI: 10.1111/j.1440-1681.2007.04575.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Endothelin‐1‐mediated Impairment of Contractile Activity in Hypertension

Abstract: 1. The present study examined the potential for reduced exercise capacity observed in hypertensive patients as a result of elevated levels of endothelin (ET)-1. We have previously reported that ET-1 exerts low-dose stimulatory or high-dose inhibitory effects on the metabolism of the rat isolated perfused hindlimb from its vasoconstrictor activity. 2. Herein, we determined whether there are similar effects on tension development by the rat isolated constant-flow hindlimb during ET-1-mediated vasoconstriction. 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Excessive vasoconstriction by endothelin in hypertension and the metabolic syndrome may prevent appropriate insulin-mediated haemodynamics and also impair basal metabolism [83]. Further, we have shown that high levels of endothelin-1 can also reduce exercise capacity in muscle, likely due to the fact that oxygen and fuel access to the muscle is impaired with excessive vasoconstriction [113].…”
Section: Hypertensionmentioning
confidence: 89%
“…Excessive vasoconstriction by endothelin in hypertension and the metabolic syndrome may prevent appropriate insulin-mediated haemodynamics and also impair basal metabolism [83]. Further, we have shown that high levels of endothelin-1 can also reduce exercise capacity in muscle, likely due to the fact that oxygen and fuel access to the muscle is impaired with excessive vasoconstriction [113].…”
Section: Hypertensionmentioning
confidence: 89%
“…While diabetic patients have defects in exercise capacity [2], this can be improved by either exercise training, or agents that improve insulin sensitivity. Certain hormones can be upregulated in metabolic disease, such as endothelin-1 in hypertension, and excessive levels of endothelin-1 can reduce aerobic capacity of muscle, and impair metabolism [91], most likely through impaired blood flow. Investigations are ongoing into certain drugs that are designed to mimic exercise.…”
Section: Negative or Neutral Outcomes Of Exercisementioning
confidence: 99%